National Health Interview Survey, 1991: Unintentional Injuries Supplement ([Verlag nicht ermittelbar], 1993)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1991 [ICPSR 6049]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Variables unique to the supplement cover two major areas: head injuries and falls. Regarding head injuries, questions were asked about loss of consciousness, number of head injuries in the past, medical care received for the most recent injury, overnight stay in the hospital as a result of this injury, number of nights in the hospital, and whether transfer to a rehabilitation center was necessary. In addition, questions were asked about where the injury occurred, whether it occurred at work, what caused the injury, and whether it happened while participating in a sports activity or physical exercise. With respect to falls, questions were asked about the number of falls in the last 12 months, whether a hip had been broken in a fall, the number of falls that had kept the respondent in bed for at least a half-day, and whether medical care had been received for injuries resulting from a fall.